Peningkatan Hasil Belajar IPA Peserta Didik Materi Rangkaian Sederhana Melalui Metode Diskusi di Kelas VI SD Negeri 122/X Sungai Beras Semester Ganjil Tahun Ajaran 2022/2023 - Aprialis R (Journal on Education, 2022)
This study aims to describe and obtain information on improving science learning outcomes through the discussion method. This research is a classroom action research which consists of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementing, observing and reflecting. The subjects of this study were 29 grade VI students at SD Negeri 122/X Sungai Beras. This research was carried out in the odd semester of the 2022/2023 academic year. Data collection techniques using tests, observation, and documentation. Data were analyzed using percentages. The results of the study showed that discussions could improve science learning outcomes for class VI students at SD Negeri 122/X Sungai Beras by replacing group members.